Evolución e cambios na normativa oficial do galego (1982-2007) - autor, Sin (Madrygal. Revista de Estudios Gallegos, 2008)
In this article we are going to analyse the changes produced in the official rules of the Galican language since its declaration as an official language in the 1982’s Statute of Autonomy till our days. After having done a brief historical introduction, we will look for the criteria and the reasons that justified those changes end we will talk about some social aspects of these rules.
Keywords: Official rules; standard language; official language